A taxonomic revision of loxocarpus (gesneriaceae) / Yao Tze Leong - Yao, Tze Leong (2012)
Henckelia sect. Loxocarpus is a small taxon consisting of c. 26 taxa distributed in West Malesia. The present study is the first comprehensive taxonomic revision for all species of Loxocarpus. This study has four objectives. The first one is to provide a review of macro-morphological diversity and variation within Loxocarpus. Second, to carry out phylogenetic analyses to determine whether Loxocarpus is distinct from or is a section within Henckelia based on DNA sequences and morphological data. Third is to provide a full taxonomic revision of Loxocarpus. And last, to provide ecology and phytogeographic perspectives of Loxocarpus species and their conservation status. Molecular phylogenetic studies showed that Loxocarpus is distinct from Henckelia and nested within a few Asian and Malesian twisted-fruited genera clade. However, it is paraphyletic. This finding is in contrast with morphological data analysis result which showed the monophyly of Loxocarpus species. In the taxonomic revision, Loxocarpus is reinstated as a genus with a revised generic circumscription. Twenty three species are recognised in this taxonomic treatment, including 15 species formerly described as Loxocarpus species are reinstated, 5 new combinations are made, 6 species are synonymised with one recognised as a variety, 4 species are determined as novelties, and 6 incompletely known taxa are enumerated. A key to all species and regional keys are provided to aid species identification. Species descriptions with full synonymy, geographic distribution with distribution maps, habitat and ecology information are given. Identification lists for herbarium specimens is provided. iv Based on corolla morphology, Loxocarpus species were divided into two informal groups ‗A‘ and ‗B‘. This grouping to a certain extent correlates with phylogenetic analysis results and distribution pattern. Morphological characters were assessed in the light of their taxonomical value. Molecular phylogenetic analyses were based on a dataset of two markers, namely trnL-F intron spacer and Internal Transcribed Spacer (ITS). Twenty samples from Loxocarpus species were included as ingroup, 31 taxa were selected from ‗Asian and Malesian twisted group‘ as outgroup. Two analysis methods, namely Bayesian Inference and Maximum Parsimony, were implemented. Ecological aspects of Loxocarpus species are presented. Study showed that habit is correlated with habitat. Pollination and dispersal as inferred from morphology and observation are discussed. Most probably, Loxocarpus species are pollinated by Trigona bees and seeds are dispersed by rain-drop ballistic. The Riau Pocket was determined as the centre of highest species diversity. Seventeen out of 24 taxa are narrowly endemic (c. 71 %). Conservation status for all species was assessed and 5 out of 24 taxa (c. 21 %) fall within ‗threatened‘ categories. The three important research questions (Section 1.2) were answered in this study. First, it is distinct from Henckelia/Codonoboea and warrants generic status. Second, Loxocarpus is a paraphyletic taxon. Third, the characters circumscribing Loxocarpus are expanded so that the genus now includes species with longer (> 10 mm) capsules.